Respuestas

2013-11-13T09:09:37+01:00
1) 25p3 - 2p2  - 4p3 + 8p2 -  9 +  p =
= 25 p^3 - 4 p3 - 2 p^2 + 8 p^2 + p - 9 =
= 21 p^3 + 6 p^2 + p - 9

2) 17 -  6 m3n2 + 8m3n2 + 6 - m3n2  =
= - 6 m^3 n^2 + 8 m^3 n^2 - m^3 n^2 + 17 + 6 = 
= m^3 n^2 + 23 

3)  -71a3b -  84a4b2  + 50a3b + 84a4b2 - 45a3b+18a3b  = 
= - 84a4b2 +  84a4b2 - 71a3b + 50a3b - 45a3b + 18a3b = 
= - 48a3b

4)  m2 + 71mn - 14m2 - 65mn + m3 - m2 - 115m2 + 6m3 = 
= 6m3 - 14m2 - m2 - 115m2 + 71mn - 65mn =
= 6m3 - 130m2 + 6mn



^2 = elevado a 2